Women's awareness of river water quality and their vulnerability to use of Brantas River water - Budirahayu, Tuti; Susanti, Emy; Sutinah, Sutinah; Kuntari, Satiti; Wicaksono, Dimas Prasetianto (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
This study was motivated by river water pollution which has an impact on the health of residents who live along the Brantas River Watershed (DAS). Aim of this research is to determine the health awareness and vulnerability of women and their families who live in the Brantas Watershed. An ecofeminist perspective is used to explain women's awareness and participation in protecting the environment and river water. This research uses a descriptive method with a survey research type. The research was conducted in Surabaya City and Sidoarjo Regency. The number of respondents was 200 housewives aged 19 to over 55 years. The research results show that there are still 11.50% of women in Sidoarjo Regency, and 3.40% from Surabaya who use river water and consider it suitable for household needs. Women and their families are also vulnerable to disease, where 35.30% of children from respondents in Surabaya have experienced skin diseases, and 34.2% of children from respondents in Sidoarjo have experienced diarrhea. However, it turns out that women also care about protecting and preserving the environment. This study concludes that efforts are needed to increase women's awareness so that they can avoid behavior that is not beneficial to health, especially in their interactions with polluted river water.